Sistem Informasi Potensi Wilayah pada Badan Pusat Statistik Kabupaten Pidie: Pengembangan dan Penerapan Teknologi Informasi untuk Efisiensi Pengolahan Data - Salfitri, Eka; Ahmad, Lukman; Akbar, Rizaldi (Jurnal Manajemen Sistem Informasi (JMASIF), 2024)
Data on regional potential plays a crucial role in decision-making processes related to regional development. The Central Bureau of Statistics (BPS) is responsible for collecting and processing data concerning natural resources, socio-economic conditions, and infrastructure in various regions. However, at BPS Pidie Regency, challenges remain in processing regional potential data, particularly in terms of efficiency and accuracy. The manual processes, combined with limited tools, pose significant obstacles to expediting data processing. Consequently, the development of the Regional Potential Information System (SIPW) has been identified as a solution to these issues. SIPW aims to enhance the efficiency and accuracy of data processing by utilizing current information technology. With SIPW, the processing of regional potential data can be automated and integrated, thereby reducing the errors common in manual methods. Furthermore, SIPW provides policymakers with quick, easy, and accurate access to data, thereby supporting more effective development planning. This study aims to develop and evaluate the implementation of SIPW at BPS Pidie Regency and assess its impact on the efficiency and accuracy of regional potential data processing. It is anticipated that SIPW will serve as an effective tool for formulating data-driven policies, ultimately fostering more targeted and efficient regional progress.